PENINGKATAN MOTIVASI SPEAKING SISWA DENGAN MENERAPKAN MODEL ROLE PLAY DI KELAS XI IPA SMA NEGERI 11 MUARO JAMBI - Ed Wardani; Epi Hardita (Sosio Akademika: Journal of Sosial Sciences and Islamic Studies, 2023)
Motivation is a desire or desire that arises from within to achieve goals by each individual or group so that plans that are embedded in the heart will be encouraged to be carried out quickly to the maximum. Student learning motivation is influenced by the learning media used by the teacher and the appropriate methods and models for conveying material. The purpose of this study was to find out the Increase in Students' Speaking Motivation by Applying the Role Play Model in Class XI IPA at SMA Negeri 11 Muaro Jambi. The use of this research is to see how to increase students' speaking motivation by implementing the Role Play Model in Class XI IPA at SMAN 11 Muaro Jambi. The methodology used in this study is Classroom Action Research, collecting data using observation and interview methods in class. Data processing techniques in this study used descriptive qualitative analysis techniques for data in the form of documents on student work, lists of student scores, observation sheets, and questionnaires. While the research problem is the use of role-playing models can improve the English students' speaking skills in class XI IPA of SMAN 11 Muaro Jambi. The results showed that with the Role Play Model in a fun learning atmosphere, student learning outcomes increased by 14.31%. It was concluded that the role-playing model could improve the speaking skills of English students at SMAN 11 Muaro Jambi.